The role of fathers and care-giving arrangements in informal settlements in Kenya and Ethiopia - Owino, George Evans; Yigezu, Moges (Frontiers in Public Health, 2023)
Introduction Quality childcare has been associated with multiple long-term benefits for children including improved school readiness, better educational outcomes and improved health and productivity. Evidence suggests that returns on investment are much higher when targeted at the youngest children, especially during the first 1,000 days. Despite the evidence and the ever-increasing need and potential benefits, investments made so far to make high-quality childcare accessible to the neediest families are not commensurate. It is estimated that nearly 350 million eligible pre-primary school-age children have no access to quality childcare, especially in low-and middle-income countries. The purpose of this study was to establish the role of fathers and the childcare arrangements in selected urban informal settlements in Kenya and Ethiopia. Methods A mixed methods design was adopted with quantitative data being collected using a structured household questionnaire administered to 635 mothers of children of 0–3 years from both countries. In both countries, data was collected from three vulnerable communities namely urban informal settlements, large commercial agricultural settlements associated with flower farms, and female penal institutions where women with young children below 4 years old are incarcerated. Quantitative data was not collected from the penal institutions because during the time of the study (at the height of the Covid-19 pandemic), access to members of the public including researchers was restricted and so here only qualitative data was collected. The data reported in this article therefore does not include data from penal institutions. Results Findings show that fathers played a major role in childcare according to 74% of respondents in Kenya and 57.7% in Ethiopia. This involvement is mainly defined in terms of providing financial support for basic needs for the family and child and for accessing health care. Some fathers were found to be either minimally involved or not involved at all. Key reasons advanced for minimal engagement included fathers having either left home permanently, had another family, was working far from home or was working long hours. Findings regarding care arrangements established that significant proportions of children had been left behind without adult supervision. Neighbors and siblings younger than 18 years provided most of the alternative care. House helps also accounted for 20.3% of care in Ethiopia with none being registered for Kenya. Daycare services only accounted for 13.4% of care in Kenya and 6.3% in Ethiopia, respectively. Conclusion The findings revealed that fathers are fairly involved in childcare even mainly through providing necessary resources. Significantly high proportions of children were left under the care of their underage siblings leading to questions of the safety of these children. Parents and guardians in these settlements had access to a mix of care arrangements including both unpaid and paid neighbors, toddler’s siblings and in limited cases, daycare services. The low levels of utilization of daycare services indicate either limited services or inability to pay for the same. It is recommended that governments consider investing in childcare services in informal settlements.